Concentration and pH-modulated dual fluorescence in self-assembled nanoparticles of phototautomerizable biopolymeric amphiphile - Lim, Chang-Keun; Seo, Jangwon; Kim, Sehoon; Kwon, Ick Chan; Ahn, Cheol-Hee; Park, Soo Young (ELSEVIER SCI LTD, 2011)
A dual-emissive biopolymeric amphiphile (GC-HBO) has been prepared by densely conjugating hydrophilic glycol chitosan (GC) with a phototautomerizable hydrophobic dye (a derivative of 2-(2'-hydroxyphenyl) benzoxazole, HBO) showing excited-state intramolecular proton transfer (ESIPT). Ratiometric modulation of phototautomeric (enol-keto) dual emission, governed by the chromophoric aggregation state, was studied with a low-molecular-weight model compound (GA-HBO) and was well correlated with the nanoparticle-forming behavior of GC-HBO via amphiphilic self-assembly in water. It has been found that the promoted chromophoric aggregation at higher concentration or at basic-to-neutral pH assists the nanostructure formation to generate predominant keto emission while the enol emission is intensified at lower concentration or with decreasing pH by disintegration of self-assembled structure. The assembly-related advantageous potential of GC-HBO for probing self-concentration and surrounding pH has been demonstrated with the ratiometric determination of critical particulation concentration (0.04 kg m(-3)) and near-physiological pH sensitivity (pK(a) similar to 5.1). (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: INTRAMOLECULAR PROTON-TRANSFER; GLYCOL CHITOSAN NANOPARTICLES; ORGANIC NANOPARTICLES; EMISSION; STATE; 2-(2' -HYDROXYPHENYL)BENZOXAZOLE; SYSTEM; PROBE